Selective laser oxidation sintering of cuprous oxide - Asif Ur Rehman; Abid Ullah; Tingting Liu; Rashid Ur Rehman; Metin Uymaz Salamci; Wenhe Liao (Materials Letters: X, 2023)
Laser powder bed fusion (LPBF) has revolutionized many industries. In this paper, we report a new approach of LPBF for oxide ceramics with selective oxidation that reduces cracks and manufacturing defects. In this method, laser energy density was used to control the oxidation within the material article. Cuprous oxide was additively manufactured into CuO with remarkable crack reduction and improvement in microstructure. The effect of process parameters on the microstructure of Cu2O and its oxidation behavior toward energy beam of different laser powers were analyzed. The experimental results clarified that the oxidation was increased by increasing the laser power in the presence of oxygen.